(untitled) (Journal of the College of Basic Education, 2025)
This current research aims to identify the effect of the "I know and I don’t know" strategy on developing reading comprehension skills among second-year middle school students. The researcher adopted the experimental method as a methodology for his research, and a design with partial control, which is the non-randomized control group design with pre- and post-test. The research community was determined by the second-grade middle school students in the middle and day schools of the Baghdad Education Directorate, Al-Rusafa I.The researcher intentionally chose Al-Khulafa Al-Rashidin Middle School, affiliated with the Baghdad Education Directorate, Al-Rusafa I. After the researcher visited the school, he found that it included three classes for the second-grade middle school, from which the researcher randomly chose a class (C) The number of its students is (42) students representing the experimental group who will study using the I know and I don’t know strategy, while the choice was made for Section (B) to represent the control group and the number of its students is (42) students who will study using the traditional method. Thus, the research sample is (84) students. After preparing the research requirements, the experiment was implemented from 11/7/2024 to 1/12/2025, with one class per week for both groups. The researcher identified nine topics from the reading and texts material for the first course, and formulated (108) behavioral objectives. He prepared model teaching plans, consisting of nine plans to teach the experimental group using the “I know and I don’t know” strategy, and nine plans to teach the control group using the traditional method. The researcher prepared an achievement test to measure the comprehension skills of second-year middle school students, consisting of (33) paragraphs, consisting of (31) objective paragraphs and (2) essay paragraphs. The test consisted of (21) multiple-choice objective paragraphs and (10) paragraphs. Choose the appropriate meaning for each word. The validity and reliability of the test were verified.